Promoting innovation adoption in the agricultural sector: the case of Lithuania and the Czech Republic - Žaneta Karazijienė; Miglė Eleonora Černikovaitė (Agricultural and Resource Economics, 2025)
Purpose. The purpose of the study – to assess the differences in agricultural innovativeness in Lithuania and the Czech Republic and to explain the need and ways of promoting agricultural innovativeness in both countries.